Reading Blackness as a Rhizome with Toni Morrison’s Preface to The Black Book - Mukherjee, Laboni (Radical Teacher, 2025)
This teaching note proposes the teaching of Gilles Deleuze and Felix Guattari’s concept of the rhizome in conversation with the marginalization of certain communities and their liberation from oppressive narratives and structures. It focuses on the rhizome’s relation to blackness and black people. It argues that anti-black society’s narration of blackness corresponds with a “root-book” and fixes blackness in a closed, interiorized narrative of slavery and racism only. It then presents black people’s escape from this anti-black narrative and their act of connecting “blackness” to other assemblages like entertainment, sports, science and technology, everyday life, food, and so on. The teaching note illustrates the above argument by placing the rhizome in conversation with Toni Morrison’s “Preface” to The Black Book in the literary theory classroom. It introduces blackness as being in a state of “in-betweenness” as opposed to having a linear narrative trajectory with slavery as its beginning. It also studies the scrapbook form of The Black Book, and states how this form is ideal for the study of the rhizome’s formal characteristics of exteriority and lacking specific beginnings and endings. It concludes with the physical book’s limitations in encapsulating the entire rhizome of blackness and champions the need for multitextuality in an anti-racist classroom.